Modern Chemical Routes for the Controlled Synthesis of Anisotropic Bimetallic Nanostructures and Their Application in Catalysis - Bhol, Prangya; Bhavya, M. B.; Swain, Swarnalata; Saxena, Manav; Samal, Akshaya K. (Frontiers in Chemistry, 2020)
Bimetallic nanoparticles (BNPs) have attracted greater attention compared to its monometallic counterpart because of their chemical/physical properties. The BNPs have a wide range of applications in the fields of health, energy, water, and environment. These properties could be tuned with a number of parameters such as compositions of the bimetallic systems, their preparation method, and morphology. Monodisperse and anisotropic BNPs have gained considerable interest and numerous efforts have been made for the controlled synthesis of bimetallic nanostructures (BNS) of different sizes and shapes. This review offers a brief summary of the various synthetic routes adopted for the synthesis of Palladium(Pd), Platinum(Pt), Nickel(Ni), Gold(Au), Silver(Ag), Iron(Fe), Cobalt(Co), Rhodium(Rh), and Copper(Cu) based transition metal bimetallic anisotropic nanostructures, growth mechanisms e.g., seed mediated co-reduction, hydrothermal, galvanic replacement reactions, and antigalvanic reaction, and their application in the field of catalysis. The effect of surfactant, reducing agent, metal precursors ratio, pH, and reaction temperature for the synthesis of anisotropic nanostructures has been explained with examples. This review further discusses how slight modifications in one of the parameters could alter the growth mechanism, resulting in different anisotropic nanostructures which highly influence the catalytic activity. The progress or modification implied in the synthesis techniques within recent years is focused on in this article. Furthermore, this article discussed the improved activity, stability, and catalytic performance of BNS compared to the monometallic performance. The synthetic strategies reported here established a deeper understanding of the mechanisms and development of sophisticated and controlled BNS for widespread application.